Motor Listrik 3 Fasa Sebagai Penggerak Mesin Cooling Fan di PT. Polychem Indonesia Tbk. - Kalika Khaldan Nurshofa; Suhendar Suhendar (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2026)
The chemical industry's production process generates significant heat, requiring a cooling system to maintain equipment stability. One component of the cooling system is the cooling fan in the cooling tower, which is driven by a three-phase induction motor. This study aims to evaluate the operational condition of the three-phase induction motor as the cooling fan drive at PT. Polycham Indonesia Tbk., focuses on the parameters of voltage, current, and bearing temperature. The research methods used were direct field observation, temperature measurements with infrared devices, current measurements with clamp meters, and interviews with experienced technicians. The measurement results show that the motor voltage is in the range of 387-396 V, which is relatively stable and still within normal limits. The motor current measurement also shows normal conditions because it does not exceed the limit value (In). The temperature of the front, middle, and rear bearings is in the range of 33-44°C, which is still far from the 75°C limit, indicating that the cooling system is working properly. Based on the analysis results, preventive maintenance recommendations are needed in the form of periodic checks on the cooling system, bearing lubrication, and monitoring of current and voltage to prevent further damage. This study emphasizes the importance of implementing sensor-based motor condition monitoring to maintain the reliability of cooling tower operations and ensure the smooth running of production processes in the chemical industry.